The exteroceptive organisation level of ontogenesis: Becoming of the system of leading development functions (Actual Problems of Psychology in Educational Institutions, 2021)
This article examines the becoming of a system of leadingfunctions for an exteroceptive level of organization. Exteroceptive meansconcerning the initial period of infancy, without taking into account itsempirical specifics. As for the becoming, in addition to the considered level,the four previous ones are taken as a basis. And finally, the very content ofbecoming is derived from the configuration of the interaction cycles of theintra-level layers, which acts as a system of leading functions. Defining theultimate goal for which the proposed scheme of analysis itself was created,it is seen as the basis for describing the exteroceptive organisation level.
Keywords: ontogenesis, multi-level periodisation, exteroceptive organisation level, obiekt as level formation, extrapolation a initial function, infancy as initial period